Thermal processed Crassostrea gigas impact the mouse gut microbiota - Suisui Jiang; Mingyong Zeng; Yuanhui Zhao (Journal of Functional Foods, 2020)
Food processing naturally accompanies with Maillard reaction and generates advanced glycation end products (AGEs), which are linked with the gut microbiota and human health. The study aimed to investigate how oysters cooked by different heating processes affected the mice microbiome. AGEs levels and lipopolysaccharides in mice feces fed with baked and fried oysters were higher than others. Additionally, Desulfovibrio and Helicobacter were increased in the fried and baked oyster diet groups (p < 0.05). In contrast, steamed oyster supplementation exhibited a high abundance of Bifidobacterium, Faecalibaculum, and Roseburia related to SCFAs-producing. The Bifidobacterium was the specific genus of bacteria in the raw oyster diet group. The correlation analysis revealed that Desulfovibrio and Helicobacter were positively correlated with the pro-inflammation cytokines. Overall, fried and baked oysters’ consumption might influence host health via increasing harmful bacteria. This study provides a deeper understanding of the influence of different processed oysters on gut microbiota.